RANCANG BANGUN MEDIA PEMBELAJARAN ILMU SHOROF BERBASIS WEB - Shabira Syifa Syurafaa Samual; Fivi syukriah; Jamilah, Jamilah; Desy Kristyawati (Jurnal Ilmiah Teknik, 2024)
Schools such as SDIT (Integrated Islamic Elementary School), MI (Madrasah Ibtidaiyah), SMPIT (Integrated Islamic Junior High School), MTs (Madrasah Tsanawiyah), SMAIT (Integrated Islamic High School), MA (Madrasah Aliyah) are schools with a higher percentage of religious studies compared to other public or private schools. One of the religious lessons in the Islamic school is Arabic. Of course, it is not easy to learn Arabic because Arabic is not a daily language used in Indonesia either at school or at home. Arabic is like any other language that has vocabulary, substitutes, basic word changes and others. When they are in middle school or equivalent to junior high school and MTS, students have begun to learn the science of shorof and dhomir (substitute words). This causes students to learn more Arabic in various media, one of which is learning through the website. The purpose of creating this website is as an alternative for students in learning shorof. The development of this website uses the SDLC (Software Development Life Cycle) method using the HTML programming language. With this website, students can learn shorof with more enthusiasm.